2021
DOI: 10.1016/j.paid.2021.111062
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress of the COVID-19 pandemic and adolescents' depression symptoms: The moderating role of character strengths

Abstract: The outbreak of COVID-19 could increase adolescents' psychological distress and have a detrimental effect on their mental health. However, the negative effect of the COVID-19 pandemic on adolescents' mental health might be moderated by their existing psychological resources. The present study sought to investigate whether the relationship between adolescents' perceived stress of the COVID-19 pandemic and their depression symptoms was alleviated by their character strengths. A total of 617 adolescents were recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 43 publications
3
35
0
2
Order By: Relevance
“…The findings of this study showed the effectiveness of CBT on increasing psychological well-being and re- With the advent of the COVID-19 Pandemic, the issue of student management strategies to effectively and appropriately control their emotions during psychological well-being crises has become a vague and urgent issue (26). As suggested in previous studies high levels of perceived stress can harm adolescents' mental health and even their physical health (2). The high prevalence of mental problems in students has caused many concerns.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The findings of this study showed the effectiveness of CBT on increasing psychological well-being and re- With the advent of the COVID-19 Pandemic, the issue of student management strategies to effectively and appropriately control their emotions during psychological well-being crises has become a vague and urgent issue (26). As suggested in previous studies high levels of perceived stress can harm adolescents' mental health and even their physical health (2). The high prevalence of mental problems in students has caused many concerns.…”
Section: Discussionmentioning
confidence: 50%
“…On March 11, 2020, the World Health Organization declared the novel coronavirus (COVID-19) prevalence a global pandemic (1). The COVID-19 pandemic has led to worsening of mental health among the general population (2). In addition, the outbreak of the COVID-19 pandemic has had widespread impacts on individual wellbeing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the sensation of becoming more caring for family members has grown. Previous studies also supported this result, finding where social support increased during the outbreak (El-Zoghby et al,2020;Liu & Wang, 2021). Furthermore, other studies conducted by Loades et al (2020) also indicate that the sluggish progress of the outbreak causes individuals to bond and seek support.…”
Section: Social Support Received By Nursing Students During Covid-19 ...supporting
confidence: 55%
“…Previous studies conducted at the beginning of the pandemic reported that depression and anxiety played a significant role in the emotional and psychological states of the population [53]. A study [54] found a positive correlation between stress during the pandemic and depression. In turn, character strength plays a significant role in stress and depression management.…”
Section: Discussionmentioning
confidence: 93%